(In)effective leadership? Exploring the interplay of challenges, goals and measures in the context of school improvement. Issue 4 (5th April 2021) - Böse, Susanne; Brauckmann-Sajkiewicz, Stefan
Abstract : Purpose: This study aims to explore the extent to which schools principals serving disadvantaged communities in Germany are able to set appropriate goals and choose suitable measures for improving their schools according to the specific challenges they face. The authors determine whether principals are able to identify their schools' challenges or whether they merely follow "universal recipes" of the school effectiveness research paradigm regardless of their particular school context. This effectiveness-driven accountability approach requires an in-depth evaluation of the school and its stakeholders and might lead to a new attitude toward failure that sees it as an essential part of developing effective school improvement plans. Design/methodology/approach: The authors conducted descriptive and correlative analyses as well as exploratory and confirmatory factor analyses using longitudinal data of 164 school principals. Through cross-sectional analyses, the authors investigated the connection among challenges, goals and measures and how they correlated with (self-reported) improvements. Findings: From a leadership perspective, priorities for school improvement should be aligned with the school-specific challenges they identify and the goals they set to address them. Research limitations/implications: The extent to which legislation concerning individual school quality development programs can translate into feasible and effective actions is unclear. Caution should be taken when interpreting the findings of this study, as they reflect school principals' self-selected evaluation measures and therefore might be biased. Practical implications: In future research, emphasis should be placed on school management processes, in particular, the development of strategic decision-making, structuring of target perspectives and derivation of steps in school improvement and instructional development. The authors recommend the government offer school principals appropriate and adequate training and support services to prevent them from overburdening their staff. Originality/value: This paper contributes to a deeper understanding of processes concerning strategic leadership, as opposed to operative management, of schools by revealing context-sensitive considerations.